IMPROVEMENT OF NUMERACY AND ACCOUNTING LITERACY THROUGH FINANCIALLY CONTEXTUALIZED LEARNING ASSISTANCE - Zalikha; Noviyanti (CV. Naskah Aceh, 2026)
This community service activity aims to improve numeracy and accounting literacy through contextual financial-based learning assistance. The background of this program is the low level of numeracy skills and basic accounting understanding among students and community members, which affects their ability to manage financial information in daily life. The activity was implemented using a mentoring approach that integrates mathematical concepts with basic accounting practices through real-life financial contexts. Data were collected through observation, interviews, and documentation. The results indicate that contextual learning assistance effectively enhances participants’ understanding of numeracy concepts, financial calculations, and simple accounting records. In addition, participants demonstrated increased motivation and confidence in applying numeracy and accounting skills in practical financial situations. Therefore, contextual financial-based learning assistance is recommended as an effective approach to strengthen numeracy and accounting literacy in educational and community settings.